2016
DOI: 10.3109/14767058.2016.1145207
|View full text |Cite
|
Sign up to set email alerts
|

Does platelet mass influence the effectiveness of ibuprofen treatment for patent ductus arteriosus in preterm infants?

Abstract: Our data suggest that platelet count, MPV and platelet mass did not affect the closure of hsPDA with ibuprofen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Platelet dysfunction or defective platelet formation was found to result in persistent DA . Several studies have also reported an association between thrombocytopenia in the first few day of life and PDA in preterm infants, but similar analyses failed to confirm these findings . Two meta‐analyses noted a significant association between low platelet count and hemodynamically significant PDA (hsPDA) on the first day of life, and between pre‐treatment thrombocytopenia and pharmacological treatment failure, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet dysfunction or defective platelet formation was found to result in persistent DA . Several studies have also reported an association between thrombocytopenia in the first few day of life and PDA in preterm infants, but similar analyses failed to confirm these findings . Two meta‐analyses noted a significant association between low platelet count and hemodynamically significant PDA (hsPDA) on the first day of life, and between pre‐treatment thrombocytopenia and pharmacological treatment failure, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…38 Several studies have also reported an association between thrombocytopenia in the first few day of life and PDA in preterm infants, [38][39][40][41] but similar analyses failed to confirm these findings. [42][43][44][45][46][47] Two meta-analyses noted a significant association between low platelet count and hemodynamically significant PDA (hsPDA) on the first day of life, and between pre-treatment thrombocytopenia and pharmacological treatment failure, respectively. 48,49 Term neonates with altered platelet number or function including Wiskott-Aldrich syndrome, alloimmune thrombocytopenia, or Glanzmann thrombasthenia, do not show an increased incidence of PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in another meta‐analysis, platelet count appeared lower in premature infants who did not respond to the first medical treatment . In the following limited number of studies, the role of platelet indices in ductal patency was investigated, but no clear relationship was found . There is also scant data regarding the value of plateletcrit (PCT) in PDA.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the following limited number of studies, the role of platelet indices in ductal patency was investigated, but no clear relationship was found. [7][8][9][10][11] There is also scant data regarding the value of plateletcrit (PCT) in PDA.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that platelet count and functions play an important role in the closure of ductus arteriosus, while some others did not find any relationship between the ductal closure and platelet count and functions. [6][7][8] High platelet count and mean platelet volume (MPV) have been shown to support ductal closure by promoting thrombosis inside the lumen of arterial duct. Large platelets are known to be more active.…”
Section: The Fate Of Patent Ductus Arteriosus Is Notmentioning
confidence: 99%